KETIMPANGAN JENDER DALAM AKSES PELAYANAN KESEHATAN RUMAH TANGGA PETANI PEDESAAN: KASUS DUA DESA DI KABUPATEN TEGAL, JAWA TENGAH - MARIYONO, JOKO; KUNTARININGSIH, APRI; SUSWATI, ENNY (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 2 Juli 2008)
The role of woman in rural and agricultural development is very important because more than a half of work in agriculture and rural areas is carried out by woman labors. Consequently, the women ought to have equity in right with men to get health services. But, there is a strong hypothesis that women have less access to health services than men because of social and cultural factors in rural areas. This study aims to examine the gender disparity and discrimination of health. The disparity is measured using concentration curve and concentration index, whereas the discrimination is approached using microeconomic theory of consumption. The results of indicate that there is a small difference in health disparity between women and men; even women get more portion than men. This is because women have specific characteristics in terms of health problem, in which men do not have.
Keywords: Health Disparity, Health Discrimination, Concentration Index